1995
DOI: 10.1021/bi00012a029
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Matrix Protein ARBP Recognizes a Novel DNA Sequence Motif with High Affinity

Abstract: ARBP is a nuclear protein that specifically binds to matrix/scaffold attachment regions (MARs/SARs). Here we characterize by DNase I footprinting, dimethyl sulfate protection, and mobility shift assays two binding sites for ARBP within a chicken lysozyme MAR fragment. Our results indicate that ARBP recognizes a novel DNA sequence motif containing the central sequence 5'-GGTGT-3' and flanking AT-rich sequences. Binding occurs through major groove contacts to two guanines of the central sequence. Collective and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 52 publications
1
31
1
Order By: Relevance
“…Studies of a number of prokaryotic and eukaryotic DNA-binding proteins have demonstrated that insertion of an ␣-helix into the major groove is a frequent mode of binding. It was previously shown that ARBP recognizes a specific motif in the lysozyme MAR through contacts in the major groove (5). Methylation protection experiments furthermore indicate that recognition of specific base pairs in the major groove is significant for binding of ARBP to two high-affinity binding sites in mouse satellite DNA as well (see below and Fig.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Studies of a number of prokaryotic and eukaryotic DNA-binding proteins have demonstrated that insertion of an ␣-helix into the major groove is a frequent mode of binding. It was previously shown that ARBP recognizes a specific motif in the lysozyme MAR through contacts in the major groove (5). Methylation protection experiments furthermore indicate that recognition of specific base pairs in the major groove is significant for binding of ARBP to two high-affinity binding sites in mouse satellite DNA as well (see below and Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Summarizing our footprint data, we first point out that the results did not reveal the seven CpGs of the sequence as high-affinity binding sites but revealed two sites, I and II, that have similarities to the ARBP binding site core consensus in the lysozyme 5Ј MAR (5). Only one of these sites (site I) contains a CpG in its center.…”
Section: ϫ9mentioning
confidence: 77%
See 2 more Smart Citations
“…MAR-binding proteins include lamins, which are found in the nuclear pore-lamina and internal matrix , topoisomerase II, SATB1, HET (SAF-B), and attachment region binding protein which is an internal matrix protein or nuclear matrin (Pommier et al, 1990;Nakayasu and Berezney, 1991;von Kries et al, 1991;Luderus et al, 1992;Buhrmester et al, 1995;.…”
Section: Het (Saf-b)mentioning
confidence: 99%